ANALYSIS OF PROFESSIONAL CONTINUING EDUCATION OPPORTUNITIES IN HEALTH CARE - Puķīte, Margarita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Any health care specialist – physician, physician’s assistant,nurse, nurse’s aid, midwife and other professionals of this field have to improve their professional skills, therefore it is important to go on learning to acquire the latest medical ideas and topicalities in the speciality, to get new knowledge, skills and competences. Professional growth and compliance with the respective field are assessed by a certification commission of any association and a certificate awarded which allows to do work in a health care field. The awarded certificate to a health care specialist serves as acknowledgement to one’s knowledge, skills and competences. In order to ease the ways for a specialist to improve knowledge, skills and competences, various courses, seminars and conferences are organized. By participation in these events specialists are awarded continuing education points, which have to be summed up thus giving an opportunity to prolong the the term for the acquired certificate. Themes for continuing education programme are offered specifying particular fields of health care .It allows a specialist to choose those programmes which give a chance to ease the solution of the most topical problems in practice